Pengaruh Harga Kredibilitas Religiusitas Kualitas Produk dan Kualitas Layanan Terhadap Minat Transaksi pada Produk Paytren di Kota Yogyakarta - Al Haq Kamal; Ahmad Yunandi; Fahmi Muqoddas Saputra (Jurnal Rekoginisi Ekonomi Islam, 2022)
The development of the use of applications or non-cash payment instruments (fintech) received special attention by Bank Indonesia. The development of non-cash payments is expected to reduce the burden of using cash which will further increase the efficiency of the economy in society. The purpose of this study was to determine how the effect of price, credibility, religiosity, product quality, and service quality on the interest in Paytren product transactions in Yogyakarta City. This research is important because researchers want to see how developments in the 4.0 era, especially developments in the fintech field. This research method uses descriptive quantitative research methods. In this study, researchers used primary data, where primary data was obtained by distributing questionnaires using Google Form and then filled in by respondents with a population of partners or agents or users of the Paytren payment application in Yogyakarta City, with a total sample of 100 respondents. The variables of this study are 6 variables each with 5 dependent variables (x) including price, credibility, religiosity, product quality, and service quality and 1 independent variable (y), namely transaction interest. The data is then processed using theapproach Partial Least Square (PLS)and using the Smartpls version 3.0 software. By using the method above, the results of this study based on regression coefficient analysis (t-statistic and p-value) show that price has a positive but insignificant effect, credibility has a positive and significant effect, religiosity has a negative and insignificant effect, product quality and service quality have a positive effect. and significant to transaction interest. Then the r-square analysis resulted in 69% of the variable (x) in this study affected the variable (y) and the rest was influenced by other variables (x).